Tinjauan Pemberian Kompensasi terhadap Kepuasan Karyawan di PT. Ecogreen Oleochemicals Batam Plant Berdasarkan Grade - Kwan Yenny Ade Wijaya; Liem Yenny Bendatu (Jurnal Titra, 2014)
PT. Ecogreen Oleochemicals Batam Plant (PT. EOB) has a variety of benefit schemes, but has not been doing employee satisfaction survei on these benefits. This research accommodating the needs by doing an employee survey at Rank and File and Supervisor Level. Survey results were analyzed using the Importance Performance Analysis (IPA). Results from the IPA shows the median value for all the interest benefit is six (very important). This indicates employees are not able to give the appraisal of importance wisely. Housing allowance, newborn child vaccination, position benefit, and the cost of prenatal care are considered important but the level of satisfaction is low. So these benefits should be the focus of improvement. In addition, the employee’s opinion also surveyed in connection with the plan to replace the medical benefit with BPJS Kesehatan. It was found that most of the employees did not know BPJS clearly so the socialization of BPJS Kesehatan is proposed.